Synthesis and characterization of isoprene oligomers to compare different production chemical processes - Pires,Renata Vieira (2019)
Abstract Three methods to obtain isoprene oligomers were evaluated: chemical degradation of non-vulcanized coagulated natural rubber; chemical degradation of natural rubber latex; and oligomerization of the isoprene monomer. The products were characterized by infrared spectrometry (FTIR), nuclear magnetic resonance (NMR) and size-exclusion chromatography (SEC). All the three processes were efficient and can be controlled in order to obtain products with desired molar mass. Among the degradation processes, the reaction with the non-vulcanized rubber led to the purest products, but this process has the disadvantage of relatively higher catalyst cost of the catalyst. Reactions of isoprene with free radical initiation produced oligomers under specific conditions: low isoprene concentration, low initiator concentration, and xylene as solvent. The results discussed here allows the readers to have a chemistry overview and experimental insights about different chemical routes to obtain isoprene oligomers, compiled together in the same work. It shall be helpful for applied chemistry researches.